2012
DOI: 10.4161/cib.19034
|View full text |Cite
|
Sign up to set email alerts
|

Novel roles for GlcNAc in cell signaling

Abstract: N-acetylglucosamine (GlcNAc) has long been known to play important roles in cell surface structure. Recent studies are now revealing new functions for GlcNAc in cell signaling. Exposure to GlcNAc regulates virulence functions in the human fungal pathogen Candida albicans and in pathogenic bacteria. These signaling pathways sense exogenous GlcNAc and are distinct from the O-GlcNAc signaling pathways in mammalian cells in which increased levels of intracellular GlcNAc synthesis leads to post-translational modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 33 publications
1
42
0
Order By: Relevance
“…Indeed, soils are generally carbon-rich and nitrogen-poor environments (Hodgson, 2000); GlcNAc-containing polymers are a rich source of both these essential nutrients. morphogenesis in Candida albicans (Gilmore et al, 2013;Naseem et al, 2011); (ii) siderophore biosynthesis, antibiotic production and sporulation in streptomycetes (Colson et al, 2008;Craig et al, 2012;Nazari et al, 2013;Rigali et al, 2006Rigali et al, , 2008Świątek et al, 2012a, b); (iii) altering the expression of virulence factors in pathogenic Escherichia coli (Barnhart et al, 2006;Sohanpal et al, 2004), amongst others (Konopka, 2012;Naseem et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, soils are generally carbon-rich and nitrogen-poor environments (Hodgson, 2000); GlcNAc-containing polymers are a rich source of both these essential nutrients. morphogenesis in Candida albicans (Gilmore et al, 2013;Naseem et al, 2011); (ii) siderophore biosynthesis, antibiotic production and sporulation in streptomycetes (Colson et al, 2008;Craig et al, 2012;Nazari et al, 2013;Rigali et al, 2006Rigali et al, , 2008Świątek et al, 2012a, b); (iii) altering the expression of virulence factors in pathogenic Escherichia coli (Barnhart et al, 2006;Sohanpal et al, 2004), amongst others (Konopka, 2012;Naseem et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…GlcNAc does not have to be catabolized to induce hyphal growth, because a strain lacking the genes needed for GlcNAc metabolism (hxk1D nag1D dac1D) can be induced to form hyphae (Naseem et al 2011. This led to the proposal that cells sensitively distinguish exogenous GlcNAc taken up from the environment vs. GlcNAc synthesized inside the cell, because exogenous GlcNAc is not phosphorylated whereas cells only synthesize phosphorylated forms of this sugar (e.g., GlcNAc-6-PO4) (Naseem et al 2012). Previous studies suggested that the cAMP pathway might be involved in GlcNAc signaling, since a cyr1D mutant that lacks adenylyl cyclase is not induced by GlcNAc to form hyphae.…”
mentioning
confidence: 99%
“…N-Acetylglucosamine (GlcNAc) is another host environmental cue and a potent inducer of both filamentation and the opaque phenotype in C. albicans. GlcNAc functions primarily through the cAMP signaling pathway in the regulation of both filamentation and white-opaque switching (16,(19)(20)(21).…”
mentioning
confidence: 99%